1994
DOI: 10.1002/pd.1970140918
|View full text |Cite
|
Sign up to set email alerts
|

Fetal renal vein thrombosis, hydrops fetalis, and maternal lupus anticoagulant. A case report

Abstract: Hydrops fetalis with fetal renal vein thrombosis in a mother with antiphospholipid antibody syndrome detected post-partum suggests an underlying pathogenetic association that may provide new strategies for treatment of a lethal disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It has been suggested that some cases diagnosed in neonates likely began in utero, based on the chronic appearance of the sonographic findings after birth. 6,7,15 Case reports of fetal renal vein thrombosis support this hypothesis, 4,5,[10][11][12][13]16,17 as do cases of fetal IVC thrombosis associated with renal vein thrombosis. [18][19][20] Many of the various case reports of fetal renal vein thrombosis were summarized in a recent review.…”
Section: Discussionmentioning
confidence: 86%
“…It has been suggested that some cases diagnosed in neonates likely began in utero, based on the chronic appearance of the sonographic findings after birth. 6,7,15 Case reports of fetal renal vein thrombosis support this hypothesis, 4,5,[10][11][12][13]16,17 as do cases of fetal IVC thrombosis associated with renal vein thrombosis. [18][19][20] Many of the various case reports of fetal renal vein thrombosis were summarized in a recent review.…”
Section: Discussionmentioning
confidence: 86%
“…Only 5 cases of venous thrombosis were reported in the studies included in this review [1, 79, 19]. We observed 1 case of a neonate [8] who developed thrombosis in the aorta, left renal artery, middle cerebral artery, and superior sagittal sinus.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 21 cases reported, 9 mothers had APS and among them, 1 developed SLE after pregnancy and another was diagnosed with APS only because of the clinical manifestations observed in her newborn [1, 2]. Despite having no history of thrombotic events, 6 other case reports demonstrated positivity of at least 1 antiphospholipid antibody; these 6 mothers were healthy, which suggests the de novo production of antiphospholipid antibodies by the neonates [7, 911, 13, 16–22]. Within the case reports, anti-cardiolipin antibody appeared to be the most common disease-associated antibody, and its presence was detected in 62% of the newborns.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, no clear causal factor was found for the fetal distress. Maternal morbidities present in the other cases were diabetes mellitus associated with pyelonephritis, gastroenteritis, preeclampsia, meconial peritonitis, gestational diabetes, disseminated lupus erythematosus, 9 and fetal hydrops due to a cytomegalovirus infection. 10 …”
Section: Discussionmentioning
confidence: 99%